Structural and immunological impacts of TOLLIP nsSNPs: A computational biology approach to drug discovery and immune system modulation - Habib, Obaid; Ishaq, Saqib; Habib, Kamran; Khattak, Aishma; Yang, Wei; Li, Zesong; Bukhari, Kainat; Ullah, Amin; Ahmad, Ajaz; Ali, Qurban (PLOS ONE, 2025)
Toll-Interacting Protein (TOLLIP) serves as key adaptor molecule in innate immune signaling, modulating toll-like receptors (TLRs) and interleukin-1 (IL-1) pathway. Despite its central role, the functional impact of non-synonymous single nucleotide polymorphism (nsSNPs) on TOLLIP remains unclear. Using an integrated computational approach, we screened 150 TOLLIP nsSNPs through consensus predictive tools including PROVEAN, PANTHER, SNPs & GO and SIFT. This approach identified four high confidence deleterious variants (R28Q, T40M, P59L, and R200C) with strong potential to compromise TOLLIP protein stability and function. Structural analysis and energy minimization suggested subtle confirmation changes and destabilizing effect, while TM-align displayed preservation of overall folding (TM-score >0.99, RMSD <0.54 Å). Evolutionary conservation, phylogenetic analysis, and protein-protein interaction (PPI) analysis underscored the functional and confirmation importance of these residues. Notably, molecular docking and dynamic simulations revealed that T40M and R200C variants significantly enhance binding affinity for the Afimetoran. Additionally, molecular dynamics (MD) simulations highlighted the altered flexibility, solvent accessibility and modified hydrogen bonds in mutant proteins structure, suggesting potential mechanisms for functional disruption. Collectively, these findings elucidate the structural and functional consequences of nsSNPs on TOLLIP protein stability, and provide a rational base for targeted therapeutic strategies in immune related diseases.